Effect of straw and plastic mulches on growth and yield of zero tillage potato (Solanum tuberosum L.) in the Coastal Khulna Region of Bangladesh - Saimon, A. H.; Mannan, M. A.; Sultana, S.; Mondal, A. R. (International Journal of Horticultural Science, 2024)
A randomized complete block design experiment was undertaken at the field laboratory of the Agrotechnology Discipline, Khulna University, Khulna, from November 2021 to March 2022 to ascertain the impact of various mulch treatments on zero tillage potato cultivation. The experiment employed BARI Alu 78 as the planting material and utilized three replications with five distinct mulch treatments. These mulch treatments were identified as follows: Straw mulch (T1), Mulch film (T2), Black polythene (T3), White polythene (T4), and Blue polythene (T5). The metrics that were recorded included the number of sprouts, plant height, number of leaves per plant, leaf width, leaf length, number of tubers, tuber length, tuber breadth, number of defective tubers, weight of defective tubers, and tuber weight. Different mulching techniques significantly influenced the overall crop yield and the underlying factors that influenced the results. The mulch film treatment resulted in the highest yield, with a production of 34.76 tons per hectare, followed by black polythene (28.11 tons per hectare), straw mulch (23.74 tons per hectare), white polythene (20.44 tons per hectare), and blue polythene (18.66 tons per hectare). The economic analysis revealed that mulch film had a high benefit cost ratio along with high input and output. Black polythene came in second place when the benefit cost ratio was compared to that of mulch film and the rest of the three treatments. Combining zero tillage with mulch film or black polythene demonstrates significant potential for becoming a cost-effective practice in the coastal region of Bangladesh.